2022
DOI: 10.1002/jev2.12238
|View full text |Cite
|
Sign up to set email alerts
|

Identification of storage conditions stabilizing extracellular vesicles preparations

Abstract: Extracellular vesicles (EVs) play a key role in many physiological and pathophysiological processes and hold great potential for therapeutic and diagnostic use. Despite significant advances within the last decade, the key issue of EV storage stability remains unresolved and under investigated. Here, we aimed to identify storage conditions stabilizing EVs and comprehensively compared the impact of various storage buffer formulations at different temperatures on EVs derived from different cellular sources for up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 58 publications
6
100
0
Order By: Relevance
“…The eventual return to a more negative plateau toward the end of the study period could reflect the surface charges of the remainder of the LRNVs that remained mostly whole and had yet to fragment or lose the outer anionic surface proteins. These trends are supported by other reported studies where EV storage resulted in a reduced concentration and increased ζ-potential over time. Size changes were more variable with one study reporting small increases of 10 nm in diameter, while others reported no observable size change. ,, These studies hypothesized membrane protein degradation to be the main mechanism of loss of EV yield, which could have similar implications for the colloidal stability of the LRNVs in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The eventual return to a more negative plateau toward the end of the study period could reflect the surface charges of the remainder of the LRNVs that remained mostly whole and had yet to fragment or lose the outer anionic surface proteins. These trends are supported by other reported studies where EV storage resulted in a reduced concentration and increased ζ-potential over time. Size changes were more variable with one study reporting small increases of 10 nm in diameter, while others reported no observable size change. ,, These studies hypothesized membrane protein degradation to be the main mechanism of loss of EV yield, which could have similar implications for the colloidal stability of the LRNVs in this study.…”
Section: Discussionsupporting
confidence: 89%
“…However, the −80°C storage method in PBS is not optimal as evidenced by Corso et al 29 The authors evaluated different EVs preservation strategies for up to 2 years, and found that over time, EVs in PBS had much lower recovery rates and that EVs degradation in PBS had already started within minutes of storage. The recommended buffer system, among several tested, was PBS plus human albumin and trehalose (PBS-HAT), which significantly improved short- and long-term EVs sample preservation at −80°C, maintained stability, and significantly improved EVs recovery rates during subsequent EVs studies.…”
Section: Sevsmentioning
confidence: 99%
“…Strategies may be implemented in order to prolong the stability and shelf-life of EVs, such as the addition of trehalose and human albumin to EV suspensions. Trehalose, in particular, is a natural sugar that stabilizes proteins, cell membranes, and liposomes, decreases intracellular ice formation during freezing and prevents protein aggregation, being widely used in the food and drug industry, which recently revealed the capacity to prevent aggregation and cryodamage of EVs [ 223 , 224 ], as well as improving the short-term and long-term storage of EVs when combined with human albumin [ 225 ]. Nevertheless, only a few studies to date have addressed the storage of EV products.…”
Section: Future Perspectivesmentioning
confidence: 99%